Breathing Effect via Solvent Inclusions on the Linker Rotational Dynamics of Functionalized MIL‐53. Issue 59 (22nd September 2021) - Tang, Jing; Chu, Yueying; Li, Shenhui; Xu, Jun; Xiong, Wenpeng; Wang, Qiang; Deng, Feng
Abstract: The breathing effects of functionalized MIL‐53‐X (X=H, CH3, NH2, OH, and NO2 ) induced by the inclusions of water, methanol, acetone, and N, N‐dimethylformamide solvents were comprehensively investigated by solid‐state NMR spectroscopy. 2D homo‐nuclear correlation NMR provided direct experimental evidence for the host‐guest interaction between the guest solvents and the MOF frameworks. The variations of the 1 H and 13 C NMR chemical shifts in functionalized MIL‐53 from the narrow pore phase transitions to large pore forms due to solvent inclusions were clearly identified. The influence of functionalized linkers and their host‐guest interactions with the confined solvents on the rotational dynamics of the linkers was examined by separated‐local‐field MAS NMR experiments in conjunction with DFT theoretical calculations. It is found that the linker rotational dynamics of functionalized MIL‐53 in narrow pore form is closely related to the computational rotational energy barrier. The BDC‐NO2 linker of activated MIL‐53‐NO2 undergoes relatively faster rotation, whereas the BDC‐NH2 and BDC‐OH linkers of activated MIL‐53‐NH2 and MIL‐53‐OH exhibit relatively slower rotation. The host‐guest interactions between confined solvents and MIL‐53‐NO2, MIL‐53‐CH3 would significantly induce an increase of the order parameters of unsubstituted carbon and reduce the rotational frequency of linkers. This study provides a spectroscopic approach for the investigation of linker rotation in functionalized MOFs at natural abundance with solvents inclusions. Abstract : The breathing effects of functionalized MIL‐53 induced by the inclusion of water, methanol, acetone, and N, N‐dimethylformamide solvents were comprehensively investigated by solid‐state NMR spectroscopy. The alteration of NMR chemical shifts indicates the phase transitions from narrow pore to large pore forms. The host‐guest interactions between confined solvents and MIL‐53‐NO2, MIL‐53‐CH3 would significantly reduce the rotational frequency of linkers.